Parametric evaluation of shear strength parameters on the stability of cut slope: a case study from Mahabaleshwar road section, India (Journal of Nepal Geological Society, 2016)
Stability of rock cut slopes depends upon the type of material, discontinuity attributes and geometry present in any location. Although, gravity remains the constant important factor in dictating the slope failure but other parameters like shear strength and available shear stress along the slope also decides the stability of the slopes to great extent. The strength of the material comes from the internal bonding between the mineral grains, contact between the particles and the ability of the material to respond to the stress conditions. Variation of these material attributes fluctuate the cohesion and angle of internal friction that constitutes the most important properties in defining the strength of any material. Rock resists shear stress by these two internal mechanisms. Numerical simulation by Finite Element Method technique is attempted for assessing the stability cut slope. An attempt has been made in this study to document the behavior of strength of the material in terms of stability of slopes by parametric study of cohesion and internal friction. This study carried to understand how the factor of safety changes with reference to change in cut slope height, cohesion and internal friction of the discontinuities that attributes the shear strength of discontinuities. The study is based on Finite Element Modeling (FEM). From the study it is found that factor of safety has strongly proportional relation with cohesion and internal friction but shown inversely proportional relation with height of cut slope.